2020
DOI: 10.3390/nu12103204
|View full text |Cite
|
Sign up to set email alerts
|

Fiber and Prebiotic Interventions in Pediatric Inflammatory Bowel Disease: What Role Does the Gut Microbiome Play?

Abstract: The etiology of inflammatory bowel disease (IBD) is complex but is thought to be linked to an intricate interaction between the host’s immune system, resident gut microbiome and environment, i.e., diet. One dietary component that has a major impact on IBD risk and disease management is fiber. Fiber intakes in pediatric IBD patients are suboptimal and often lower than in children without IBD. Fiber also has a significant impact on beneficially shaping gut microbiota composition and functional capacity. The impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 107 publications
(159 reference statements)
0
21
0
1
Order By: Relevance
“…Prebiotics has been previously proved to ameliorate intestinal inflammation. In vitro and in vivo studies provided using prebiotics as a therapy for IBD via their anti-inflammatory activities (Valcheva et al, 2015, Healey, 2020, Le et al 2020. The role of prebiotic fibers in reducing intestinal inflammation is associated with the stimulation of the growth of gut probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics has been previously proved to ameliorate intestinal inflammation. In vitro and in vivo studies provided using prebiotics as a therapy for IBD via their anti-inflammatory activities (Valcheva et al, 2015, Healey, 2020, Le et al 2020. The role of prebiotic fibers in reducing intestinal inflammation is associated with the stimulation of the growth of gut probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…and a decrease populations of total anaerobes or Clostridia in the feces were observed when the pigs were fed diets containing 0.5% fructo-oligosaccharide in combination with Bifidobacterium longum (Clarke et al, 2017). Small intestine is mainly responsible for food digestion and absorption, while large intestine is important for microbial fermentation of substances (Healey et al, 2020). Hindgut of pigs and humans contain a larger proportion of Firmicutes than small intestine, indicating that large intestine might undertake a crucial role in microbial fermentation of dietary fiber (Flint et al, 2008).…”
Section: Dietary Fibers and Gut Microbiotamentioning
confidence: 99%
“…Greater populations of Escherichia-Shigella and Streptococcus are always considered as pathogenic bacteria related to host infection and enteric diseases, such as diarrhea symptoms. Thus, occurrences of enteropathies are primarily associated with microbial composition in the upper gut (Healey et al, 2020).…”
Section: Dietary Fibers and Gut Microbiotamentioning
confidence: 99%
“…Previous studies have demonstrated that prebiotics and fiber beneficially modulate the gut microbiome and reduce inflammation in IBD [19][20][21] . Inulin-type fructans (IN) appear to be particularly promising in enhancing clinical outcomes in adult IBD patients, suppressing inflammation as well as modulating the composition and function of the gut microbiome 22,23 .…”
Section: Introductionmentioning
confidence: 99%